Systematic Design of Electronics Ballast - บุญเจียม, ไพศาล (Frontiers in Engineering Innovation Research, 2006)
This paper presents a novel design of electronics ballast. The selection criteria stem from ballast specifications as well as operation characteristics and constraints. Lamp rated power. minimum lamp ignition voltage. filament heating current and zero voltage tum on operation of the inverter switches are used as criteria for load circuit component selection. Fundamental frequency approximation analytical technique and linear lamp model are used to establish the circuit equations. The experimental results show that approximation analysis is good enough for primary design.